(untitled) (Journal of Parents and Teachers, 2023)
Within the programs related to inclusive education that a center can carry out with the aim of responding to the diversity of its students, the therapeutic pedagogy program becomes a benchmark in this regard, since through individualization of teaching tries to give a personalized response to students with special educational needs so that they can fully develop their full potential.